Medicinal Plants, Parasites and Snails in Health - Adewunmi, Clement O. (Obafemi Awolowo University Press, 2013)
The dominion of man over living and non-living things is the major attribute possessed by him in conquering his environment and space. This lecture titled “Medicinal Plants, Parasites and Snails in Health” deals with our efforts, and those of others in manipulating plants, parasites and snails for better health. Plants and animals suffer from a range of parasites, including protozoa; nematodes. arthropods-and fungi. They show a variety of protective adaptation. Some plants produce chemicals - phytoalexins - specifically in response to attack by micro-organisms and parasites. The anti-nematode effect reported for known phytoalexins suggests that these compounds have nematostatic rather than a nematocidal effect.